2021
DOI: 10.1177/0896860821996096
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of peritoneal dialysis-related peritonitis rates over time from national or regional population-based registries and databases

Abstract: Peritoneal dialysis (PD)-related peritonitis is one of the top priorities for care and research among PD stakeholders. This study summarizes PD peritonitis rates from available population-based national or regional registries around the world, examining trends over time. This is a systematic review of PD peritonitis rates in patients treated with PD for kidney failure, from census-based national or provincial/statewide/provider registries or databases. MEDLINE (via PubMed) was searched from inception to August… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
26
0
9

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 35 publications
3
26
0
9
Order By: Relevance
“…However, this finding was an association only, with uncertain causality, bearing in mind that PD practice and penetration was likely to be very different between continents. 91 Collectively, as a group, the peritonitis rates (0.18 to 0.40 episodes per patient-year) for ASEAN countries appeared to be similar to those studied in the Peritoneal Dialysis Outcomes and Practice Pattern Study (0.26 to 0.38 episodes per patientyear). 52 The results of HRQOL studies showed that higher-income countries (Brunei, Singapore and Malaysia) tend to show that PD patients have a better quality of life, consistent with trends in developed countries.…”
Section: Demographicssupporting
confidence: 54%
“…However, this finding was an association only, with uncertain causality, bearing in mind that PD practice and penetration was likely to be very different between continents. 91 Collectively, as a group, the peritonitis rates (0.18 to 0.40 episodes per patient-year) for ASEAN countries appeared to be similar to those studied in the Peritoneal Dialysis Outcomes and Practice Pattern Study (0.26 to 0.38 episodes per patientyear). 52 The results of HRQOL studies showed that higher-income countries (Brunei, Singapore and Malaysia) tend to show that PD patients have a better quality of life, consistent with trends in developed countries.…”
Section: Demographicssupporting
confidence: 54%
“…In the 1980s, the introduction of peritoneal dialysis (PD) into clinical practice [14,15], raised the question of which RRT should have been preferred in potential KT recipients [16][17][18][19]. Main concerns regarding the routinary use of PD in this particular population were the presence of peritoneal scarring due to previous abdominal surgery, the risk of peri-operative peritonitis [20,21] or exit-site/tunnel infections [20,22], the higher susceptibility to post-transplant diabetes mellitus [23,24], the possible development of encapsulating peritoneal sclerosis [25,26], and the perceived increase in graft thrombosis [23,[27][28][29]] and acute rejection rates [16,30].…”
Section: Introductionmentioning
confidence: 99%
“…La péritonite reste la complication la plus urgente et la plus sévère de la dialyse péritonéale (DP). Au cours des deux dernières décennies, les améliorations apportées à la technique et à la prise en charge des patients ont réduit la probabilité de péritonite à un niveau historiquement bas [1]. Malgré ces progrès, la péritonite représente encore jusqu'à 5 % des causes de décès en DP [2] et sa prévention est une priorité pour améliorer les résultats centrés sur le patient [3,4].…”
Section: Introductionunclassified
“…Malgré l'importance du taux de péritonite en DP, seule une minorité d'administrations sanitaires mesurent et déclarent les taux de péritonite [1]. Ceci est en grande partie dû aux difficultés rencontrées par les centres de DP pour calculer leur taux de péritonite, soit par mauvaise compréhension de la formule, soit par manque des données nécessaires.…”
Section: Introductionunclassified
See 1 more Smart Citation